If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6 = -98 + -10 Reorder the terms: 6 + 3x = -98 + -10 Combine like terms: -98 + -10 = -108 6 + 3x = -108 Solving 6 + 3x = -108 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3x = -108 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = -108 + -6 3x = -108 + -6 Combine like terms: -108 + -6 = -114 3x = -114 Divide each side by '3'. x = -38 Simplifying x = -38
| 20-12x=10x+8 | | 2+3x/7+2-x/2=19/14 | | 3x^2-6*2x+9=0 | | 4d=25/4+7 | | -2x+7=-11-4x-9 | | 3(3x+4)=2(9+3x) | | 3x-5x+2x=-7+9 | | =4(2-3)-3(2z+1) | | 2(x-4)=-x+5-13+3x | | 4y^2-x^2=11 | | 3n-1n=5n-9 | | 7+(a-1)(a+5)= | | 8y+y-5y= | | 2X+Y+3=0 | | 3n/8=16 | | 92/x-7=16 | | 2x-7x+64=29-10x-5x | | Y-5X=4 | | -2y-8x=1 | | 4w+9=49 | | 7-3x=10-2x | | z^2-4z+13=0 | | ln(2x-8)=0 | | (x-8)=-(2x-3) | | 2y+5y-7=0 | | 3(x-8)=-(2x-3) | | 13x-28=21x-13 | | (3q^5p^4/4r^7)^2 | | x/2-1=8 | | 2x+4=2+3x | | 3=(2/5)10+b | | 2.5t-8=10-3.5v |